2015
DOI: 10.1161/hypertensionaha.114.04892
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Ameliorate Intrauterine Growth Retardation in a Transgenic Rat Model for Preeclampsia

Abstract: Preeclampsia is a multisystemic syndrome during pregnancy that is often associated with intrauterine growth retardation. Immunologic dysregulation, involving T cells, is implicated in the pathogenesis. The aim of this study was to evaluate the effect of upregulating regulatory T cells in an established transgenic rat model for preeclampsia. Application of superagonistic monoclonal antibody for CD28 has been shown to effectively upregulate regulatory T cells. In the first protocol (treatment protocol), we appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…For example, interleukin 15 is tightly regulated 82 and important for vascular remodeling at the maternal fetal interface 83 for CD8 T-cell homeostasis 84,85 and for tissue-resident T-cell development. 86 Based on these findings herein, and others, 37,50 we speculate that unique interaction between immune and vascular systems is set by the experience of pregnancy and placenta-related factors 87 and continues in PP. This in turn influences subsequent susceptibility to cardiovascular stress.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…For example, interleukin 15 is tightly regulated 82 and important for vascular remodeling at the maternal fetal interface 83 for CD8 T-cell homeostasis 84,85 and for tissue-resident T-cell development. 86 Based on these findings herein, and others, 37,50 we speculate that unique interaction between immune and vascular systems is set by the experience of pregnancy and placenta-related factors 87 and continues in PP. This in turn influences subsequent susceptibility to cardiovascular stress.…”
Section: Discussionsupporting
confidence: 72%
“…[46][47][48][49] Because of these characteristics, we examined the effects of CD8 T-cell reconstitution in Rag1 ÀÀ mice. In light of the potential role played by CD4 TREGs in the immune homeostasis of pregnancy 18,50 and in the modification of cardiovascular disease, 46,[51][52][53][54] we also examined mice with genetic deficiency in CD4 T cells. 55 We chose mesenteric vessels because of their role in the regulation of systemic blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Although not completely understood yet, several studies have shown that patients with preeclampsia display decreased Treg expansion in peripheral blood and the decidua, suggesting an association between the failure of pregnancy compatible Treg transformation and the pathogenesis of preeclampsia [55][56][57][58]. In a transgenic model of preeclampsia, physiologic restoration of Tregs has been shown to improve intrauterine growth restriction without affecting hypertension and production of anti-angiogenic factors such as Flt-1 [59]. Although these results are very exciting, it is possible that overwhelming transgenic gene expression overrides the control of hypertension and other factors.…”
Section: Are Tregs Dysregulated In Preeclampsia?mentioning
confidence: 99%
“…Przybyl et al recently evaluated the effect of upregulating regulatory T cells in transgenic rat model for preeclampsia achieved by mating female rats transgenic for human angiotensinogen with rats transgenic for human renin 25 . The authors utilized a superagonistic monoclonal antibody for CD28 to upregulate regulatory T cells.…”
Section: Immune Mechanisms and Regulatory T Cells In Preeclampsiamentioning
confidence: 99%